The opportunities and limitations of using OLAP cubes for business intelligence reporting in banking - Ulaş, Onur Can. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
New rules of competition and rapid changes within the industry force banks to create new business strategies and be more efficient in making decisions. OLAP is a business intelligence technology utilized for rapid access and analysis of information from multiple perspectives. The purpose of this study was to demonstrate opportunities and limitations of using OLAP Cubes for business intelligence reporting in banking from a technological point of view. Triangulation technique on the basis of methods and data sources was adopted to enhance the validity and reliability of the study and crosscheck the findings from a particular method. First, theoretical background and related literature were reviewed. Secondly, a comparative experiment through design and development of an OLAP Cube was carried out to determine the opportunities and limitations of OLAP cubes and to reevaluate the arguments in theory. Besides, a structured questionnaire was conducted among banking IT experts to confirm the findings of the experiment. Thus, this is an explanatory, deductive and quantitative study, however, descriptive, inductive and qualitative strategies were involved as well at some points of the research. The results indicated that OLAP was more appropriate than relational model in banking due to greater query performance and simplicity in conducting complex queries with specific purposes such as management information reporting. However, it was less flexible than the relational model, which provides the ability to serve further needs and easily develop structured reports. Thus, it should be well decided which model must be used in accordance with the purpose.
Keywords: OLAP technology.; Business intelligence.